3D‐printed microneedles with open groove channels for liquid extraction. Issue 3 (28th December 2021) - Leng, Fang; Zheng, Mengjia; Xu, Chenjie
Abstract: Microneedles (MNs) offer a simple and minimally invasive way to sample skin interstitial fluid for bioanalysis. Through the integration with portable or wearable sensing devices, it allows us to get qualitative information about some biomarkers in situ. This work is to show a MN platform with open groove channels that are manufactured using photopolymerization 3D printing. The grooves on the needle surface permit that liquid flows from the tips to the base under the influence of capillary force. The ultimate MN device can penetrate skin and tissues and sample liquid in the skin model. By taking the glucose as the model biomarker, we demonstrate that the biomarkers in the extracted liquid can be analyzed in situ by the commercial test strips attached to the back. Abstract : This report describes the 3D fabrication of the microneedles with the open groove channels for skin interstitial fluid extraction through capillary force. Biomarkers in the extracted liquid (e.g. glucose) can be analyzed in situ by the commercial test strips attached to the back of microneedles.